Vrbnice (Plecoptera) in vodne muhe poplesovalke (Diptera, Empididae) reke Dragonje - Sivec, Ignac (Varstvo narave, 2002)
Faunistical list of stoneflies (Plecoptera) and aquatic dance flies (Diptera, Empidiedae) of the Dragonja River is presented. Their distribution and endangerment according to IUCN categories are briefly discused.
Keywords: Dragonja; Empididae; entomologija; Plecoptera; Slovenija; vodne muhe; vrbnice